2007
DOI: 10.1007/s00586-007-0410-2
|View full text |Cite
|
Sign up to set email alerts
|

Cervical facet joint kinematics during bilateral facet dislocation

Abstract: Previous biomechanical models of cervical bilateral facet dislocation (BFD) are limited to quasi-static loading or manual ligament transection. The goal of the present study was to determine the facet joint kinematics during high-speed BFD. Dislocation was simulated using ten cervical functional spinal units with muscle force replication by frontal impact of the lower vertebra, tilted posteriorly by 42.5°. Average peak rotations and anterior sliding (displacement of upper articulating facet surface along the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…However, motion segments do not exhibit physiological kinematics during cervical trauma (Ivancic et al, 2008;Nightingale et al, 1996;Nightingale et al, 2016;Panjabi et al, 2007), and it is important to obtain quantitative information about the mechanical response of cervical FSUs and the facets during constrained intervertebral motions to develop improved injury tolerance levels. When extrapolating these results beyond physiological limits it is important to recognize that the quasi-static rates applied in this study were substantially slower than the ~3 m/s associated with head-impact loading causing cervical injury (McElhaney et al, 1979;Nightingale et al, 1996;Van Toen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, motion segments do not exhibit physiological kinematics during cervical trauma (Ivancic et al, 2008;Nightingale et al, 1996;Nightingale et al, 2016;Panjabi et al, 2007), and it is important to obtain quantitative information about the mechanical response of cervical FSUs and the facets during constrained intervertebral motions to develop improved injury tolerance levels. When extrapolating these results beyond physiological limits it is important to recognize that the quasi-static rates applied in this study were substantially slower than the ~3 m/s associated with head-impact loading causing cervical injury (McElhaney et al, 1979;Nightingale et al, 1996;Van Toen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Such muscle forces may impose an additional intervertebral compressive load during injury that restricts traumatic flexion and intervertebral separation, causing increased loading of the facets. In contrast, superimposed intervertebral distraction during traumatic cervical motion, such as that observed during inertially-produced CFD (Ivancic et al, 2008;Panjabi et al, 2007), may reduce loading of the facets, thereby reducing the likelihood of concomitant facet fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperflexion is characterised by forward motion of the head, beyond normal craniocervical range (often with the jaw contacting the torso) as shown in figure 1A during scrum engagement and in figure 2A, and is caused by posterior to anterior forces on the head. This mechanism has been shown, in ex vivo spine investigations to result in facet joint contact and ramping of the superior facet up the inferior facet which results in distraction and flexion of the intervertebral joint and, ultimately, facet dislocation3840 and it is clearly present for forward players in the scrum.…”
Section: Cervical Spine Injury Biomechanics Literaturementioning
confidence: 98%
“…Ivancic et al 38 39 and Panjabi et al 40 have shown that flexion moments combined with axial compression and anterior shear forces (like those during scrum and causing hyperflexion) can result in facet dislocations in the lower cervical spine. In fact, several factors like the angle of head impact, initial neck posture and head constraint are all relevant to cervical spine injury from head-first impact.…”
Section: Cervical Spine Injury Biomechanics Literaturementioning
confidence: 99%
“…In recent years, articular facet biomechanics has become a topic of interest, [29][30][31][32]44,52 as significant changes in relative facet motion following trauma or surgery have been suggested to induce degenerative changes in the articular cartilage. 55,65 Although studies have investigated in vivo facet kinematics at the lumbar spine, 40,44 there are no known in vivo studies that have compared different surgical techniques on facet kinematics in the cervical spine.…”
Section: 1357mentioning
confidence: 99%